Patterns of Shear Stress Changes in Turfy Soil Modified by Biological Enzymes - Wang, Han; Lv, Yan (Journal of Research in Science and Engineering, 2025)
This study investigates the coupled effects of freeze-thaw cycles and bioenzyme modification on the shear properties of grass-turfy soils in seasonally frozen zones. Through systematic laboratory experiments, undisturbed turfy soil samples collected from a typical seasonal frozen soil area in Dunhua, Jilin Province, were subjected to Terra-Zyme enzyme treatments at concentrations of 0%, 1%, 3%, 5%, 8%, and 10%. Rapid shear tests were conducted after 0, 1, 5, 10, and 15 freeze-thaw cycles. Results indicate: (1) Freeze-thaw cycles significantly degrade the shear strength of turfy soils, with strength decay concentrated in the first five cycles before stabilizing. Both cohesion and internal friction angle exhibit declining trends, revealing the cumulative and irreversible nature of freeze-thaw damage; (2) Bioenzyme modification effectively enhances turfy soil shear properties, with an optimal dosage range. When Terra-Zyme content ranges from 3% to 5%, modified soil exhibits the most significant increases in cohesion and internal friction angle, achieving peak shear strength; (3) A coupled effect exists between freeze-thaw cycles and bioenzyme modification. Bioenzyme-modified soil retains certain strength advantages after freeze-thaw cycles, but its enhancement effect gradually diminishes with increasing freeze-thaw cycles. This study elucidates the combined influence mechanism of freeze-thaw cycles and bioenzyme modification on the shear properties of turfy soils. It provides a theoretical basis for stability design and reinforcement treatment of turfy soil foundations and subgrades in seasonally frozen regions. Practical engineering applications are recommended to adopt a bioenzyme content of 3%–5% while strictly controlling the number of freeze-thaw cycles.